Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41598-018-33220-5
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica isolates from Western Australian rangeland goats remain susceptible to critically important antimicrobials

Abstract: This study investigated faecal carriage and antimicrobial resistance (AMR) of Salmonella enterica recovered from rangeland goats. Faecal samples (n = 400) were collected at slaughter from four consignments of goats (n = 100 samples per consignment), each from one of four localities in Western Australia. Carriage of Salmonella spp. was detected in 106 samples (26.5%; 95% CI 22.4–31.0%). The rate of faecal carriage for each consignment ranged between 23–30%. PCR assays targeting the STM2755 and STM4497 genes rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…Rangeland goats are a common breed for meat production in the Australian goat-meat industry, exporting 90% of the products [83]. Al-Habsi et al [84] reported that 26.5% of the intestinal contents of 400 rangeland goats sampled at slaughter from four locations in WA contained Salmonella. S. Typhimurium was the most frequently isolated serovar, followed by S. Chester and S. Saintpaul, as shown in Table A2.…”
Section: Western Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Rangeland goats are a common breed for meat production in the Australian goat-meat industry, exporting 90% of the products [83]. Al-Habsi et al [84] reported that 26.5% of the intestinal contents of 400 rangeland goats sampled at slaughter from four locations in WA contained Salmonella. S. Typhimurium was the most frequently isolated serovar, followed by S. Chester and S. Saintpaul, as shown in Table A2.…”
Section: Western Australiamentioning
confidence: 99%
“…In this state, Al-Habsi et al [84] reported that Salmonella isolates from rangeland goats' faecal samples remained susceptible to the critically important antimicrobials tested, including ceftiofur, ceftriaxone, chloramphenicol and ciprofloxacin.…”
Section: Western Australiamentioning
confidence: 99%
“…High resistance to sulfamethoxazole observed in our study was similar to the study by Saha et al (2013) who reported that Salmonella strains associated with goats in Bangladesh were resistance to sulfamethoxazole at a rate of 66.7%. Most Salmonella isolated from goats in the studies in Tanzania and Australia were also found to be susceptible to most antimicrobials tested (Mwanyika et al, 2016;Al-Habsi et al, 2018). In contrast, reports of other researchers from different areas showed that Salmonella isolates were resistant to commonly used antimicrobials including tetracycline, nitrofurans, streptomycin, kanamycin, and ampicillin, and were resistance to multiple antimicrobials (Saha et al, 2013;Zelalem et al, 2011;Zewdu and Cornelius, 2009;Glenn et al, 2011;Bantawa et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, a moderately high prevalence of Salmonella in goats was found in previous studies in Australia. A prevalence of 26.5% was reported in Western Australian rangeland goats (Al-Habsi et al, 2018), andDuffy et al (2009) reported the prevalence of Salmonella in carcass swabs, rumen, and feces from goats at two Australian abattoirs to be at 28.9% (35/121), 45.5% (55/121) and 46.3% (56/121), respectively. Differences or similarity in farming practice, healthy or diseased state, type of sample, and/or isolation method may be responsible for prevalence observed in the reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, antimicrobials are considered to play a major role in enhancing productivity; however, there is also a longterm, but often unknown, risk to food production from overusing some antimicrobials in agriculture, including antibiotics. In Australia, studies show that the occurrence of AMR in animal production is currently relatively low (Abraham et al 2014;Al-Habsi et al 2018;Abraham et al 2019;Barlow et al 2015;Sahibzada et al 2020;Wallace et al 2020). The low level of AMR in livestock in Australia is likely due to the relatively strict regulation of antimicrobials in food animals and high biosecurity standards (Barlow et al 2015).…”
Section: A Typology Of Economic Analysis Of Amrmentioning
confidence: 99%